Role of imatinib in the treatment of pediatric onset indolent systemic mastocytosis: a case report. (December 2013) - Agarwala, Manoj Kumar; George, Renu; Mathews, Vikram; Balasubramanian, Poonkuzhali; Thomas, Meera; Nair, Sheila
Background: Mastocytosis is a sporadic disease characterized by an abnormal accumulation of mast cells (MCs) in single or multiple organs. It has a heterogeneous clinical picture which is a reflection of underlying tissue MC burden, mediators released and the organs involved. Here, the authors report significant symptomatic, cutaneous and systemic response to imatinib in a case of childhood onset indolent D816V KIT unmutated systemic mastocytosis (SM). Case report: A 19-year-old female presented with a history of itchy skin lesions over the face, trunk and extremities since 6 months of age associated with recurrent bouts of angioedema. The skin and bone marrow examination were consistent with mastocytosis. No pathogenic mutations were detected in exons 8 and 17. In view of the severity of cutaneous symptoms and evidence of bone marrow involvement, she was treated with imatinib which resulted in marked improvement. Conclusion: Imatinib has a therapeutic role in the presence of an imatinib-sensitive KIT mutation or in KIT816-unmutated patients with aggressive SM. Its role in the treatment of indolent and cutaneous mastocytosis is less well established. However, the authors have demonstrated the usefulness of imatinib in the treatment of c-KIT-negative indolent SM with extensive cutaneous involvement.